El proceso administrativo para la sostenibilidad de la empresa Jiménez & jiménez del cantón Zaruma. - Saca Espinosa, Gloria Elizabeth (2022)
The objective of this research work is to elaborate the proposal of the administrative process for the company Jiménez & Jiménez of the Zaruma Canton; this study began with the theoretical foundation of the variables: Administrative Process and Sustainability; and culminated with the design of the proposal of the administrative process. The research is of descriptive type, it allowed to characterize the fundamental aspects of the study and with the application of the techniques of the survey and the interview previously designed the information was obtained to carry out the situational diagnosis, in this way it was possible to demonstrate the main problems that the company faces, such as the lack of basic tools of the administrative process that causes the inadequate use of this process. In addition, it was determined that the manager of the company has been applying the administrative process in an empirical and partial way in each of its phases. With the analysis and discussion of results, the proposal of the administrative process is presented, proposing solution alternatives in each phase of Planning, Organization, Direction and Control in order to achieve the optimum organizational development and the efficient fulfillment of its objectives. It is concluded that the administrative process applied is not the correct one and there is not the necessary technical knowledge and therefore it is recommended to consider the alternatives designed in the proposal. Key Words: Administration, Administrative process, Planning, Organization, Management, Control.